IMPROVING THE METHODOLOGY OF USING MNEMONIC STRATEGIES FOR MASTERING ENGLISH VOCABULARY AMONG ESL STUDENTS - Alikberova Kamila Adhamovna (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This study investigates the effectiveness of mnemonic strategies in enhancing vocabulary acquisition among English as a Second Language (ESL) students. A total of 60 ESL learners participated in an eight-week intervention, divided into an experimental group utilizing mnemonic techniques and a control group following traditional vocabulary instruction. Pre- and post-tests measured vocabulary retention, while student surveys assessed perceptions of the learning experience. Results indicated a significant improvement in vocabulary acquisition in the experimental group (p < 0.01) and positive feedback regarding the use of mnemonics. The findings suggest that mnemonic strategies can be effectively integrated into ESL instruction to enhance vocabulary